2017
DOI: 10.2215/cjn.12311216
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of NSAIDs Use and Their Association with Other Analgesic Use in CKD

Abstract: Nonsteroidal anti-inflammatory drug use is common among patients with CKD but less so among those with worse kidney function or those who see a nephrologist. Initiation or discontinuation of nonsteroidal anti-inflammatory drugs is often associated with supplementation with or replacement by, respectively, other analgesics, including opioids, which introduces possible drug-related problems when taking these alternative analgesics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 30 publications
(28 reference statements)
0
20
0
2
Order By: Relevance
“…Three prevalence groupings were extracted that had sufficient data to complete full meta-analyses: overall analgesic use prevalence (17 studies), 14,[16][17][18]20,23,25,29,33,36,37,43,45,46,48,49,52 opioid use prevalence (13 studies), [14][15][16]18,19,21,24,26,31,37,38,40,44 and NSAID use prevalence (19 studies). 14,15,19,20,22,[26][27][28]30,32,34,35,37,[39][40][41][42]47,50 A meta-analysis was also done for acetaminophen use, which included 8 studies, 14,…”
Section: Details Of Included Studiesmentioning
confidence: 99%
“…Three prevalence groupings were extracted that had sufficient data to complete full meta-analyses: overall analgesic use prevalence (17 studies), 14,[16][17][18]20,23,25,29,33,36,37,43,45,46,48,49,52 opioid use prevalence (13 studies), [14][15][16]18,19,21,24,26,31,37,38,40,44 and NSAID use prevalence (19 studies). 14,15,19,20,22,[26][27][28]30,32,34,35,37,[39][40][41][42]47,50 A meta-analysis was also done for acetaminophen use, which included 8 studies, 14,…”
Section: Details Of Included Studiesmentioning
confidence: 99%
“…One recent study suggested that starting and stopping NSAIDs were both associated with higher odds of increased alternative analgesic use, including opioids, in patients with chronic kidney disease. 21 Moreover, inclusion of NSAIDs and celecoxib in the postoperative setting following ambulatory surgery has been found to decrease the need for rescue analgesics and improve quality of recovery and patient satisfaction. 22 Notably, no studies have previously examined the impact of nonantibiotic drug ADR reporting on drug utilization patterns and outcomes such as OUD, which have important implications for patient care and safety.…”
mentioning
confidence: 99%
“…Patients exposed to prescription and OTC NSAIDs in our cohort had a higher burden of risk factors for kidney injury as well as other side effects of this drug class. 8 A subanalysis of the Chronic Renal Insufficiency Cohort found that 24% of participants reported use of NSAIDs suggesting that despite evidence for risk, clinicians still prescribe NSAIDs. 9 Knowledge about NSAIDs and kidney risks in the general population is poor, especially with regard to OTC products.…”
mentioning
confidence: 99%